2021
DOI: 10.3390/genes12081181
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetics and Gut Microbiome: Perspectives for Multiple Sclerosis

Abstract: As a complex disease, Multiple Sclerosis (MS)’s etiology is determined by both genetic and environmental factors. In the last decade, the gut microbiome has emerged as an important environmental factor, but its interaction with host genetics is still unknown. In this review, we focus on these dual aspects of MS pathogenesis: we describe the current knowledge on genetic factors related to MS, based on genome-wide association studies, and then illustrate the interactions between the immune system, gut microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 128 publications
(207 reference statements)
0
10
0
Order By: Relevance
“…A probiotic is defined by the International Scientific Association for Probiotics and Prebiotics (ISAPP) as a “live microorganism that, when administered in adequate amounts, confers a health benefit on the host” ( 192 ). Given the involvement of the GBA in the pathogenesis of MS ( 23 ), probiotics could represent an emerging therapeutic alternative. Studies on the use of probiotics in MS are quite scarce in humans when compared to those performed on EAE.…”
Section: Probiotics Prebiotics and Postbioticsmentioning
confidence: 99%
“…A probiotic is defined by the International Scientific Association for Probiotics and Prebiotics (ISAPP) as a “live microorganism that, when administered in adequate amounts, confers a health benefit on the host” ( 192 ). Given the involvement of the GBA in the pathogenesis of MS ( 23 ), probiotics could represent an emerging therapeutic alternative. Studies on the use of probiotics in MS are quite scarce in humans when compared to those performed on EAE.…”
Section: Probiotics Prebiotics and Postbioticsmentioning
confidence: 99%
“…This is a somewhat expected result, as there is a mounting body of evidence of a bidirectional, proinflammatory relationship between MS and the gut microbiome. The pathologically composed gut microbiome of MS patients was shown to induce a proinflammatory state and, vice versa, the autoreactive immune system of the patient has been observed to shape the gut microbiome [ 388 , 389 , 390 ]. The vast majority of the biomarker candidate miRNA-target gene pairs identified by the study are already known to be involved in the activation and signalling apparatus of the immune system.…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
“…Initial studies pointed to the involvement of HLA alleles [25,26], but more recent work identified 200 loci linked to susceptibility to MS away from the HLA region [27][28][29]. Moreover, a number of studies suggest that genetic factors alone are insufficient and often require additional risk factors such as environmental ones, such as, e.g., an unhealthy gut microbiome [30]. Additional environmental factors include low vitamin D or low sun exposure, air pollution and exposure to organic solvents.…”
Section: Multiple Sclerosismentioning
confidence: 99%